Investigating the effects of product popularity and time restriction: The moderating role of consumers’ goal specificity - Yi, Cheng; Jiang, Zhenhui (Jack); Zhou, Mi (Production and Operations Management, 2023)
Online retailers employ various kinds of social and marketing information cues to influence consumers’ product interest and purchases. This study focuses on the effects of two types of information cues, product popularity and time restriction on product promotions, on consumers’ product approach behavior. It takes a unique perspective by examining how such effects change as consumers’ shopping goals become more concrete. The results of a field experiment and a laboratory experiment show that product popularity and time restriction may not always have a positive influence on consumers’ product approach behavior. In particular, when consumers have not yet formed specific shopping goals, product popularity and time restriction weaken each other's effects on users’ initial product judgment, whereas these two information cues reinforce each other's effects on consumers’ final product evaluation when consumers’ shopping goals have become more specific. This study deepens our understanding of the individual and interaction effects of product popularity and time restriction at different levels of consumer goal specificity. The findings have significant implications for how retailers can leverage different information cues for promoting products.